2008
DOI: 10.1210/jc.2007-2429
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitizers for the Treatment of Hirsutism: A Systematic Review and Metaanalyses of Randomized Controlled Trials

Abstract: Imprecise and inconsistent evidence of low to very low quality suggests that insulin sensitizers provide limited or no important benefit for women with hirsutism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 33 publications
0
43
1
9
Order By: Relevance
“…Additionally, metformin has not been shown to be an effective therapy for clinical symptoms of hyperandrogenism, such as acne or hirsutism [43]. Therefore, metformin is not recommended as a first-line treatment for management of menstrual irregularity or clinical hyperandrogenism in PCOS because of the lack of evidence for consistent benefits [37,38,44].…”
Section: Menstrual Irregularity and Clinical Hyperandrogenismmentioning
confidence: 99%
“…Additionally, metformin has not been shown to be an effective therapy for clinical symptoms of hyperandrogenism, such as acne or hirsutism [43]. Therefore, metformin is not recommended as a first-line treatment for management of menstrual irregularity or clinical hyperandrogenism in PCOS because of the lack of evidence for consistent benefits [37,38,44].…”
Section: Menstrual Irregularity and Clinical Hyperandrogenismmentioning
confidence: 99%
“…Az eddig végzett, de nem megfelelő minőségű vizsgálatok miatt további, jól megtervezett vizsgálatokra van szükség ezen a területen is [52].…”
Section: A Metformin Alkalmazásaunclassified
“…Most studies have shown no evidence of hirsutism-reducing activity of metformin [58,59], which is why this drug is not used in the management of hyperandrogenism. The principal role in the treatment of menstruation disorders is played by oral contraceptives.…”
Section: Szkolenie Podyplomowementioning
confidence: 99%